Functional Dyspepsia with Helicobacter pylori Infection - Rabbinu Rangga Pribadi; Ari Fahrial Syam; Ening Krisnuhoni (Acta Medica Indonesiana)
Helicobacter pylori infection is commonly found worldwide. In Indonesia, the prevalence of H. pylori infection is 22.1%. The bacteria are responsible for gastritis, peptic ulcer disease (PUD), and gastric cancer.Helicobacter pylori may also has a role in functional dyspepsia. Diagnostic approach consists of noninvasive and invasive examinations. One of the invasive strategy is upper gastrointestinal (UGI) endoscopy and gastric mucosa biopsy.